Just between us : women speak about their writing - Joseph, Ammu (Delhi : Women's World, India ; Hyderabad : Asmita ; New Delhi : Women Unlimited, 2004)
Interviews with 20th century Indian women authors from various languages; interviewed at many seminars on their life and works.
Keywords: Indic literature -- Congresses; Indic literature -- Congresses; Women authors, Indic -- Interviews